Making a match: Exploring the association between `ethnic match' and program utilization in a home visiting program. - Diaz, Akira. (2017)
Abstract: Culturally competent practice, including "ethnic match" in service provision, is a growing area of interest in this increasingly diverse nation. Ethnic match is often considered a means of ensuring culturally competent practice, based on the assumption that ethnic match represents shared culturally-situated perspectives between the home visitor and participant. The present mixed-methods study, based on data from the Massachusetts Healthy Families Evaluation, explores the association between ethnic match and program utilization among young mothers enrolled in a home visiting program. In addition, a sub-sample of participant interviews is qualitatively analyzed to evaluate perceptions of cultural competence on the part of these mothers' home visitors. Results show that ethnic match is not significantly related to core program utilization outcomes (e.g. duration of use, number of home visits, and intensity of use) within the full sample of program participants. Perception of cultural competence was identified in five categories: acknowledging and respecting differences; making necessary connections and referrals; connecting to intrinsic networks; educating participants about goal pursuit strategies; and customizing help. These categories were all referenced in interviews of both matched and non-matched participants; however making necessary connections and education about goal pursuit strategies were discussed more frequently among participants of the matched sample. These differences suggest fruitful avenues for further research.; Thesis (M.A.)--Tufts University, 2014.; Submitted to the Dept. of Child Development.; Advisor: Francine Jacobs.; Committee: Jayanthi Mistry, and Sarita Rogers.; Keyword: Individual & family studies.